Interprofessional Substance Use Disorder Education in Health Professions Education Programs: A Scoping Review. (March 2020) - Muzyk, Andrew; Smothers, Zachary P.W.; Andolsek, Kathryn M.; Bradner, Melissa; Bratberg, Jeffrey P.; Clark, Seth A.; Collins, Kathryn; Greskovic, Gerard A.; Gruppen, Larry; MacEachern, Mark; Ramsey, Susan E.; Ruiz Veve, Jennifer; et al.
Abstract : Purpose: The authors conducted this scoping review to (1) provide a comprehensive evaluation and summation of published literature reporting on interprofessional substance use disorder (SUD) education for students in health professions education programs and (2) appraise the research quality and outcomes of interprofessional SUD education studies. Their goals were to inform health professions educators of interventions that may be useful to consider as they create their own interprofessional SUD courses and to identify areas of improvement for education and research. Method: The authors searched 3 Ovid MEDLINE databases (MEDLINE, In-Process & Other Non-Indexed Citations, and Epub Ahead of Print), Embase.com, ERIC via FirstSearch, and Clarivate Analytics Web of Science from inception through December 7, 2018. The authors used the Medical Education Research Study Quality Instrument (MERSQI) to assess included studies' quality. Results: The authors screened 1, 402 unique articles, and 14 met inclusion criteria. Publications dated from 2014 to 2018. Ten (71%) included students from at least 3 health professions education programs. The mean MERSQI score was 10.64 (SD = 1.73) (range, 7.5–15). Interventions varied by study, and topics included general substance use (n = 4, 29%), tobacco (n = 4, 29%), alcohol (n = 3, 21%), and opioids (n = 3, 21%). Two studies (14%) used a nonrandomized 2-group design. Four (29%) included patients in a clinical setting or panel discussion. Ten (72%) used an assessment tool with validity evidence. Studies reported interventions improved students' educational outcomes related to SUDs and/or interprofessionalism. Conclusions: Interprofessional SUD educational interventions improved health professions students' knowledge, skills, and attitudes toward SUDs and interprofessional collaboration. Future SUD curriculum design should emphasize assessment and measure changes in students' behaviors and patient or health care outcomes. Interprofessional SUD education can be instrumental in preparing the future workforce to manage this pressing and complex public health threat. Abstract : Supplemental Digital Content is available in the text.